2022
DOI: 10.3389/fped.2022.1027358
|View full text |Cite
|
Sign up to set email alerts
|

A methodological and clinical approach to measured energy expenditure in the critically ill pediatric patient

Abstract: The metabolic response to injury and stress is characterized initially by a decreased energy expenditure (Ebb phase) followed by an increased metabolic expenditure (Flow phase). Indirect calorimetry is a methodology utilized to measure energy expenditure and substrate utilization by measuring gas exchange in exhaled air and urinary nitrogen. The use of indirect calorimetry in critically ill patients requires precise equipment to obtain accurate measurements. The most recent guidelines suggested that measured e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Ideally, providers can utilize indirect calorimetry (IC) to determine critically ill patients’ basal metabolic needs. IC is a more accurate method than the commonly used equation, i.e., the World Health Organization (WHO) and Schofield equations, as they are proven to be inherently inaccurate in estimating the basal metabolic rate (BMR) of neurologically critically ill children [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, providers can utilize indirect calorimetry (IC) to determine critically ill patients’ basal metabolic needs. IC is a more accurate method than the commonly used equation, i.e., the World Health Organization (WHO) and Schofield equations, as they are proven to be inherently inaccurate in estimating the basal metabolic rate (BMR) of neurologically critically ill children [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study nested within a multicenter randomized controlled trial among children with a complicated severe malnutrition in developing countries, the authors found that blood metabolomic and proteomic profiles robustly differentiated children who died ( n = 92) from those who survived ( n = 92) and these data reinforce other recent study with similar outcome ( 10 , 11 ). In this edition of Methods in Pediatric Critical Care 2022, Silva-Gburek et al discuss about a clinical and methodological approach to measure energy expenditure in the critically ill pediatric patient reviewing the utilization of indirect calorimetry, considering the gold standard method, to evaluate energy expenditure and substrate utilization by measuring gas exchange in exhaled air and urinary nitrogen ( 12 ). Regarding to cost-benefit ratio, this evaluation can measure energy requirements in a precise way and optimize nutritional therapy avoiding degradation of nutritional status and worsening prognosis.…”
mentioning
confidence: 99%
“…In an ideal framework, measured resting energy expenditure (mREE) by IC would be desirable in all patients with TBI, through sampling of oxygen consumption and carbon dioxide elimination from modern ventilators (6, 7). This remains the current recommended gold standard (8, 9).…”
mentioning
confidence: 99%